Pierce's Semiotic Interpretation of Messages â€œSudah Sampai Rumah Belum?â€ in Graffiti - Yuda Syah Putra; Irpan Riana (2023)
Graffiti is often seen as something that damages the aesthetics of a place, but in fact, graffiti has artistic value and messages contained within it. In this article, the author conducted an analysis and interpretation of a graffiti found in a corner of a city. The author used Charles Sanders Pierce's semiotic theory to analyze the signs contained in the graffiti. The results showed that the graffiti was a representation of various objects and interpretants, ranging from anxiety and restlessness to social criticism of the phenomenon of road accidents. The author also highlights the importance of understanding semiotic theory in reading and interpreting a sign. In addition, the author reveals the role of graffiti in influencing a person's thoughts and actions, as well as its relationship with social and cultural phenomena in society. This article is expected to provide a deeper understanding of graffiti and the importance of seeing it as a work of art and form of expression in society.Â